Mathematics Learning With Guided Inquiry Model Open-Oriented Problem Solving Improves Student Learning Outcomes - Purwati, Gusti Ayu Made; Sudana, Dewa Nyoman; Arini, Ni Wayan (International Journal of Elementary Education, 2020)
The low learning outcomes of mathematics are due to students' mathematics lesson problems' lack of optimal solving. One of the ways is by using a guided inquiry learning model with an open problem-solving orientation. This research aimed to determine the guided inquiry learning model's effect with open problem-solving orientation on fourth-grade elementary school students' mathematics learning outcomes. This type of research is an experimental design with a non-equivalent post-test only control group design. The study population was 180 students. The research sample was 23 students (experimental) and 23 students (control). The research sample was taken using a simple random sampling technique. The method used in collecting data on mathematics learning outcomes was a test in an essay consisting of 5 items. The data collected were mathematics learning outcomes and were analyzed using t-test. The study results were getting an average post-test result in the experimental group of 18.17 and 11.04 in the control group after being given treatment. The t-test results obtained by t-count greater than t-table (17,825> 1,680). From the results of the t-test analysis and the average learning outcomes, it can be concluded that the guided inquiry learning model with open problem-solving orientation affects the mathematics learning outcomes of fourth-grade elementary school students. This research implies that it can increase students' concentration in learning activities to foster innovative learning and add new experiences.